The pari passu principle and UK corporate insolvency law - Khan, Mohammed Asadulla (2024)
A company normally goes insolvent when it cannot satisfy the debts it owes. Upon insolvency, the pari passu principle calls for equal and proportionate repayment of debt to creditors based on their pre-insolvency entitlements. This principle is often regarded as a fundamental and central feature of the law.